Islamic Religeos Education Learning Based On Character Development At STIAMI Institute Jakarta - Nurhasan (Yayasan Sinergi Kawula Muda, 2023)
Education in Indonesia tends to only prepare students to be intellectually intelligent. So that results in many smart people but their behavior is not right. This shows that education is currently not able to optimally form affective aspects, so that the hope of realizing human beings who have noble, religious and complete character really requires special attention. The STIAMI Jakarta Institute of Social Sciences and Management has implemented Islamic religious education learning based on the character building method of the Tablighi congregation. Which is education based on the character building method of the Tabligh congregation by means of doing I'tikaf in the mosque for one day, 3 days, 10 days, 40 days, and 4 months for its citizens both in domestic and foreign mosques. This study aims to reveal the character-building based learning method of the Tabligh Congregation in realizing religious culture on campus. This study uses a qualitative approach with ethnographic methods and uses data analysis techniques, namely data reduction, data presentation and conclusions. Data was collected by means of participatory observation, in-depth interviews, and documentation. The research findings include (1) the profile of the STIAMI Institute, which is studied from the history of the STIAMI Institute, (2) the vision and mission, (3) and the character building based learning system of the Tablighi congregation method. So that the STIAMI Institute is known as one of the tertiary institutions that really pays attention to its citizens so that they have noble, religious, and strong character.